Guillain-Barré syndrome (GBS) complicated by rhabdomyolysis (RML): Case reports of 2 children and literature review - Yang, Xin-Ying; Han, Tong-Li; Lv, Jun-Lan (Frontiers in Pediatrics, 2022)
We initially described two children who developed Guillain-Barré syndrome (GBS) complicated by rhabdomyolysis (RML), and reviewed five adult patients from the literature. Through analysis of the clinical features, laboratory examination, treatment and prognostic data from these seven patients, we found that when GBS “meets” RML, the most prominent characteristics were the following: male dominance; limb weakness, pain and respiratory failure could be caused by multiple factors; limb weakness and respiratory muscle paralysis were more serious than with GBS alone; and the probability of mechanical ventilation was increased. Neuroelectrophysiological studies revealed axonal lesions. Close monitoring and timely identification and intervention to remedy potentially fatal complications such as electrolyte disorder multisystem complications and kidney injury are crucial. With plasma exchange, peritoneal dialysis and supportive treatment, the long-term outcome of most patients was satisfactory.